Serial viral load analysis by DDPCR to evaluate FNC efficacy and safety in the treatment of mild cases of COVID-19 - Renato Martins da Silva; Paula Gebe Abreu Cabral; Sávio Bastos de Souza; Raul Ferraz Arruda; Sheila Passos de Figueiredo Cabral; Arícia Leone Evangelista Monteiro de Assis; Yolanda Porto Muniz Martins; Carlos Augusto de Araújo Tavares; Antônio Brazil Viana Junior; Junbiao Chang; Pingsheng Lei (Frontiers in Medicine, 2023)
IntroductionThe SARS-CoV-2 outbreak has threatened the human population globally as the numbers of reinfection cases even after large-scale vaccination. Trials have been carried out to find drugs effective in fighting the disease, as COVID-19 is being considered a treatable disease only after we have antivirals. A clinical candidate originally developed for HIV treatment, AZVUDINE (FNC), is a promising drug in the treatment of COVID-19.MethodsTo predict the clinical outcome of COVID-19, we examined the course of viral load, every 48 h, by RT-PCR, and disease severity using an antiviral drug, FNC, with 281 participants. A randomized clinical trial was performed to evaluate the efficacy of FNC added to standard treatment, compared with placebo group added to standard treatment, for patients with mild COVID-19. RT-qPCR and ddPCR were applied to estimate the viral load in samples from patients. Also, the clinical improvement was evaluated as well as the liver and kidney function.Results and discussionNotably, the FNC treatment in the mild COVID-19 patients may shorten the time of the nucleic acid negative conversion (NANC) versus placebo group. In addition, the FNC was effective in reducing the viral load of these participants. The present clinical trial results showed that the FNC accelerate the elimination of the virus in and could reduce treatment time of mild patients and save a lot of medical resources, making it a strong candidate for the outpatient and home treatment of COVID-19.Clinical trial registrationhttps://clinicaltrials.gov/ct2/show/NCT05033145, identifier NCT05033145.